PENGARUH LATIHAN DRILL FOREHAND TERHADAP PENINGKATAN KETEPATAN PUKULAN DALAM PERMAINAN TENIS MEJA PADA SISWA SMAN 15 MEDAN - Silalahi, Anju William; Samsuddin Siregar; Otniel Zega; Roy Gonzales Siboro; Sinurat, Parlinggoman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigates the effect of forehand drill training on improving stroke accuracy in table tennis among students of SMAN 15 Medan. The forehand stroke is the most fundamental technique in table tennis, yet many students demonstrate inadequate control and consistency in execution. Drill training, characterized by systematic and repetitive motor practice, is widely recognized as an effective method for developing motor skills. Using a simple experimental design with a pre-test and post-test approach, this research involved 20 students as subjects. Data were collected through forehand accuracy tests targeting designated zones on the table. Results demonstrated a significant improvement from a pre-test mean of 58.5 to a post-test mean of 78.9, representing an average gain of 20.4 points. All subjects showed improvement without any decline in performance. These findings confirm that structured forehand drill training positively and significantly enhances stroke accuracy. The study supports motor learning theory, which posits that repetitive, directed practice strengthens neuromuscular coordination and movement automaticity. Physical education teachers are encouraged to adopt drill-based methodologies as a core instructional strategy for table tennis skill development.